Plasma Amino Acid Concentrations at Birth and Patent Ductus Arteriosus in Very and Extremely Preterm Infants - Huizing, Maurice J.; Borges-Luján, Moreyba; Cavallaro, Giacomo; González-Luis, Gema E.; Raffaeli, Genny; Bas-Suárez, Pilar; Bakker, Jaap A.; Moonen, Rob M.; Villamor, Eduardo (Frontiers in Pediatrics, 2021)
Background: Amino acids are increasingly recognized as bioactive molecules in numerous physiological and pathophysiological pathways. The non-essential amino acid glutamate is vasoactive in the rat ductus arteriosus (DA) and a decrease in its levels within the first days of life has been associated with the presence of patent DA (PDA) in extremely preterm infants. However, these findings have not been confirmed in other studies. Objective: To investigate the possible association between amino acid concentrations in the first hours of life and the presence of PDA in a cohort of 121 newborns with gestational age (GA) below 30 weeks and birth weight (BW) below 1500 g Methods: Plasma samples were collected 6-12 h after birth and amino acid concentrations were determined by tandem mass spectrometry. Besides PDA, we analyzed the potential association of amino acid concentrations with infant sex, small for GA (SGA, defined as BW